Naturally multiplying the effect of vitamin D in white mushrooms and studying its effect on intestinal microbiota and individual health - Kareem Rahi Al-Magsoosi, Suhad; Almuharib, Omar; Hussien, S.A.; Anees, H. Essa (Journal of Neonatal Surgery, 2025)
Mushrooms naturally contain vitamin D2, and exposure to UV light can enhance the amounts of vitamin D2 in mushrooms. It is crucial to acknowledge that vitamin D2 is less physiologically potent than vitamin D3 and may not offer the same advantages as vitamin D3 pills or foods containing vitamin D3. In addition, ultraviolet (UV) radiation can also lead to the deterioration of other advantageous chemicals found in mushrooms. Thus, we advise avoiding subjecting mushrooms to ultraviolet (UV) radiation for the purpose of obtaining vitamin D3 supplements. Approach The procedure entails choosing freshly harvested mushrooms from the market and quantifying their vitamin D concentration in 122-gram increments. Remove the caps and halve the mushrooms lengthwise. Once the mushrooms have been divided lengthwise, position them with the gills facing upwards on metal trays. In this orientation, the nostrils are directed upwards. Retrieve the trays and enclose the mushroom pieces in wrapping to prevent moisture accumulation. Solar exposure during the hours of 10 a.m. and 6 p.m. might result in harm. On the second day, the trays weighing 122 grammes had a vitamin D concentration. To increase the concentration, the trays were exposed to sunlight again, this time without being covered. Both males and females were seen to have an increase in vitamin D levels as a result of consuming genetically engineered mushrooms. Prior to meal consumption, the mean concentration of vitamin D3 in males was 13.4 mg/100 ml. However, after ingesting the modified food, it rose by 32 mg/100 ml. This implies that diet has a crucial impact on substantially increasing the concentration of vitamin D in the body. The initial concentration of vitamin D in women was 12.2 mg/100 ml. However, after consuming the modified diet for an entire month, the concentration climbed to 38.6 mg/100 ml. This demonstrates that the modified diet had a substantial impact on boosting the concentration of vitamin D in both genders. an edible resource. The study investigated the impact of vitamin D intake on the bacteria count in adult individuals of both genders. In men, the overall microbial count reduced dramatically to 10,000 cells/ml of culture media following ingestion, in contrast to the initial count of 13,233 cells/ml. After intake, the overall microbial count in women reduced to 12,000 cells/mL, as opposed to the initial level of 20,000 cells/ml.